In Vitro Antibacterial Activity and Phytochemical Analysis of Some Selected Medicinal Plants - Jeyaseelan, E.C (International Journal of Pharmaceutical & Biological Archive, 2010)
Medicinal plants are extensively used in traditional medicine to cure various infectious diseases in human. The present study was undertaken to investigate in vitro antibacterial activity of successively extracted hexane, dichloromethane (DCM), ethyl acetate, ethanol, methanol and aqueous extracts of bulb of Allium sativum, leaf of Eucalyptus citriodora and Ocimum sanctum against Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli at different test concentration by agar well diffusion method. The test samples were also subjected to detect the presence of phytochemicals. The results of antibacterial activity was analyzed by using one-way analysis of variance (ANOVA) and followed by Least Significant Difference (LSD) test. The study revealed that the extracts possessed antibacterial activity in a dose dependent manner. Among the test plants E.citriodora showed better activity against test bacteria. Aqueous extract of E.citriodora exhibited significantly (P < 0.05) higher effect on B.subtilis at the concentration of 0.5 mg / 100 µl. Methanol and aqueous extracts of E.citriodora on B.subtilis, ethyl acetate and ethanol extract of E.citriodora on S.aureus and methanol extract of E.citriodora on P. aeruginosa showed significantly (P < 0.05) higher effect at the concentration of 1.0 mg / 100 µl compared to other test extracts. Among the different test samples of O.sanctum, ethanol extract produced better inhibition on B.subtilis. Ethyl acetate extract of A.sativum and aqueous extract of O.sanctum showed inhibitory effect on all test bacteria at the concentration ranged from 1.0 mg / 100 µl to 30.0 mg / 100 µl. Phytochemical study revealed that tannins, alkaloids, cardiac glycosides, saponins and terpenoids are present in ethyl acetate and ethanol extracts of E.citriodora. All other test samples except hexane extracts contain at least one of the phytochemical tested. This study suggests that ethyl acetate, ethanol, methanol and aqueous extracts of E.citriodora ethyl acetate extract of A.sativum and ethyl acetate and aqueous extracts of O.sanctum can be used for further isolation and purification of active principles.